Prevalence and Factors Associated With Sex Trading Among High-Risk Substance-Involved Women Under Community Supervision in New York City - Jiwatram-Negrón, Tina (Criminal justice and behavior, 2020)
This article examines the prevalence of and factors associated with sex trading among a high-risk sample of 337 substance-involved women in community corrections enrolled in an HIV risk reduction study in New York City, using baseline data. Forty percent of the sample reported trading sex for money, food, drugs, or other resources in the prior 90 days. Multivariate logistic regression analyses showed significant associations among age, ethnic minority status, marital status, prior mental health hospitalization, binge drinking, and having recently been in jail/prison and sex trading (p < .05). Women who reported that both they and their partner recently (past 90 days) used crack/cocaine or that their partner recently used crack/cocaine were more likely to report sex trading than women who reported that neither they nor their partner recently used crack/cocaine (p < .05). Study findings underscore an urgent need for multipronged intervention efforts that simultaneously address multilevel risk exposures.